Voriconazole therapeutic drug monitoring in critically ill patients improves efficacy and safety of antifungal therapy. Issue 6 (20th July 2020) - Li, Hao; Li, Mo; Yan, Jinqi; Gao, Lan; Zhou, Linjing; Wang, Yang; Li, Qi; Wang, Jin; Chen, Tianjun; Wang, Taotao; Zheng, Jie; Qiang, Wei; et al.
Abstract: Since voriconazole plasma trough concentration (VPC) is related to its efficacy and adverse events, therapeutic drug monitoring (TDM) is recommended to perform. However, there is no report about the data of voriconazole TDM in critically ill patients in China. This retrospective study was performed to determine whether voriconazole TDM was associated with treatment response and/or voriconazole adverse events in critically ill patients, and to identify the potential risk factors associated with VPC. A total of 216 critically ill patients were included. Patients were divided into two groups: those underwent voriconazole TDM (TDM group, n = 125) or did not undergo TDM (non‐TDM group, n = 91). The clinical response and adverse events were recorded and compared. Furthermore, in TDM group, multivariate logistic regression analysis was performed to identify the possible risk factors resulting in the variability in initial VPC. The complete response in the TDM group was significantly higher than that in the non‐TDM group ( P = .012). The incidence of adverse events strongly associated with voriconazole in the non‐TDM group was significantly higher than that in the TDM group (19.8% vs 9.6%; P = .033). The factors, including age (OR 0.934, 95% CI: 0.906‐0.964), male (OR 5.929, 95% CI: 1.524‐23.062), serum albumin level (OR 1.122, 95% CI: 1.020‐1.234), diarrhoea (OR 4.953, 95% CI: 1.495‐16.411) and non‐intravenous administration (OR 4.763, 95% CI: 1.576‐14.39), exerted the greatest effects on subtherapeutic VPC (VPC < 1.5 mg/L) in multivariate analysis. Intravenous administration (OR 7.657, 95% CI: 1.957‐29.968) was a significant predictor of supratherapeutic VPC (VPC > 4.0 mg/L). TDM can result in a favourable clinical efficacy and a lower incidence of adverse events strongly associated with voriconazole in critically ill patients. Subtherapeutic VPC was closely related to younger age, male, hyperalbuminaemia, diarrhoea and non‐intravenous administration, and intravenous administration was a significant predictor of supratherapeutic VPC.